Titanoboa [videorecording (DVD)] : monster snake - Bloch, Jon; Head, Jason (Inception Media Group, 2012)
Jon Bloch joins forces with world expert in ancient snakes, Jason Head, to unlock the lost land of the Titanoboa. They explore how this monster snake would've lived by visiting its extant cousins including a foray into the Florida Everglades and the Venezuelan Grasslands to meet boa constrictors and anacondas. Their research yields some intriguing and frankly terrifying insights including the mating and predation behavior of the giant snake.